Relative age effect among males football players in FIFA World Cup 2022 - Ibrahim, Siti Aisyah; Azam, Zulkhairi; Zaki, Sufyan; Sariman, Mohd Hanifa; Sulaiman, Norasrudin; Shari, Maisarah (Faculty of Sports Science and Recreation, 2025)
The relative age effect (RAE) in sports competition refers to the continuous imbalance in birth date distribution within an age cohort, which tends to put individuals born earlier in the year at advantage of being selected into sports. The rationale for this study is that most previous research has focused on youth team sports rather than senior team sports, particularly football, and considering that RAE does have a few conflicting results in football, thus the purpose of this study is to examine the presence of RAE among male football players participating in the FIFA World Cup 2022. The secondary data on the football players, including their nationality, name, age, birthdate, and the teams they played for at the FIFA World Cup 2022, was gathered from the official FIFA website. Thus, the players' birthdates would be divided into four quartiles (Q). The present study included a sample of (N=828) male football players of FIFA World Cup 2022, all of whom had professional experience and ranged within the age range of 18 to 40 years. Most of the previous research indicated that RAE was significant in sport performance. Nevertheless, in this finding, there was no significant RAE was found on overall RAE distribution (p = 0.854), between champion and lowest ranked team (p = 0.092), and qualification to the knockout stage (p = 0.726). However, there is overrepresentation of RAE was found on overall distribution football player where post-hoc evaluation proved that Q1 had the highest value (n = 266, SR = 4.10). Followed by the overrepresentation in Q2 on the champion team (Argentina). Meanwhile, there is overrepresentation of RAE in Q1 on disqualified team. In a nutshell, this analysis demonstrates the overrepresentation of RAE in elite international football tournament, highlighting the role of RAE in selection of players that maybe down to the factors of better physique and physiology than the late born.